2021
DOI: 10.1002/agj2.20521
|View full text |Cite
|
Sign up to set email alerts
|

Delta yield–based optimal nitrogen rate estimates for corn are often economically sound

Abstract: Corn producers often overapply nitrogen (N) fertilizer to minimize risk of yield loss because of uncertainty regarding actual corn N requirements. On-farm N trials, which are simple to deploy and interpret, may enable producers to better understand their corn N fertilizer requirements. We analyzed a database of corn yield response to N trials conducted in Ontario, Canada to determine if delta yield (dY) N trials can reliably estimate economic optimum N rates (EONRs) and to assess the financial liability of dY-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Finding ways of simultaneously increasing grain yield and nitrogen use efficiency as well as reduce environmental impact has been a major challenge in maize production in the NCP. Irrigation practice and N management, and their interaction, are important parameters influencing maize productivity [8,[43][44][45][46][47]. Previous studies have shown that drip fertigation, which integrates drip irrigation and N management, can improve maize grain yields and nitrogen use efficiency concurrently [48].…”
Section: Discussionmentioning
confidence: 99%
“…Finding ways of simultaneously increasing grain yield and nitrogen use efficiency as well as reduce environmental impact has been a major challenge in maize production in the NCP. Irrigation practice and N management, and their interaction, are important parameters influencing maize productivity [8,[43][44][45][46][47]. Previous studies have shown that drip fertigation, which integrates drip irrigation and N management, can improve maize grain yields and nitrogen use efficiency concurrently [48].…”
Section: Discussionmentioning
confidence: 99%
“…Using the delta-yield approach (Janovicek et al, 2021), the observed EONR values varied from 105 to 199 kg N ha −1 (Table 1). Delta yield, meaning the difference in grain yield between a non-limiting and very low (<34 kg N ha −1 ), can be used to predict EONR accurately by taking advantage of the rectangular hyperbolic relationship between delta yield and agronomic efficiency (Janovicek et al, 2021;Lory & Scharf, 2003). Briefly, we used the following equation to predict EONR using delta yield:…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…We developed a RF model to estimate delta yield using variables which were used for developing the BN model. The RF model first predicted delta yield, which was then used to predict sidedress N rate using delta-yield equations (Janovicek et al, 2021). RF uses numerous non-parametric and classification decision trees following a process called "bootstrap aggregation" or "bagging."…”
Section: Development Of Random Forest Modelmentioning
confidence: 99%
See 2 more Smart Citations